2017
DOI: 10.3892/etm.2017.4124
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil functions in the adaptive protection of cardiac function following ischemia

Abstract: Abstract. The present study aimed to investigate the effects of remifentanil during adaptation followinsg myocardial ischemia, and its possible clinical applications. Remifentanil was used during the simulation of adaptation following ischemia, which was performed using a Langendorff heart perfusion system. A total of 75 rats were divided into five groups, and the coronary flow, cardiac output and the cardiac enzyme content in coronary effluent prior to ischemia and post-reperfusion were recorded. Electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To place semi‐quantitative values on these observations, the Flameng's scoring method was applied to quantify mitochondrial fragmentation and structural integrity. Flameng's scoring is a standard method for the assessment of mitochondrial injury and is frequently reported for mitochondrial ultrastructural evaluation in cardiac function following ischemia . The Flameng's scores for control, global ischemic reperfusion, low‐flow ischemic and Rot hearts were 0.16 ± 0.32, 2.35 ± 0.32, 2.9 ± 0.25 and 2.55 ± 0.36, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To place semi‐quantitative values on these observations, the Flameng's scoring method was applied to quantify mitochondrial fragmentation and structural integrity. Flameng's scoring is a standard method for the assessment of mitochondrial injury and is frequently reported for mitochondrial ultrastructural evaluation in cardiac function following ischemia . The Flameng's scores for control, global ischemic reperfusion, low‐flow ischemic and Rot hearts were 0.16 ± 0.32, 2.35 ± 0.32, 2.9 ± 0.25 and 2.55 ± 0.36, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Flameng's scoring is a standard method for the assessment of mitochondrial injury and is frequently reported for mitochondrial ultrastructural evaluation in cardiac function following ischemia. 28,33,34 The Flameng's scores for control, global ischemic reperfusion, low-flow ischemic and Rot hearts were 0.16 ± 0.32, 2.35 ± 0.32, 2.9 ± 0.25 and 2.55 ± 0.36, respectively (Figure 6b). The mitochondria in control hearts featured appropriately arranged myocardial fibers, mitochondria with intact cristae and intact outer membrane whereas mitochondria from ischemic and Rot hearts showed disordered myocardial fibers, different degrees of swelling, ruptured cristae with limpid and concentrated matrix and some mitochondria without complete membranes.…”
Section: Morphology Of Mitochondria Of Perfused Hearts By Temmentioning
confidence: 99%
“…Remifentanil, a highly selective μ -opioid receptor agonist, shows protective effects against ischemic injury in multiple organs, such as the liver [ 26 , 27 ], heart [ 28 , 29 ], and small intestine [ 30 , 31 ] in animals. Our previous study showed that remifentanil preconditioning attenuates hepatic IRI by increasing the expression of iNOS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even under this conditions, the administration of sevoflurane was not associated with clinically relevant benefit. Actually propofol [ 25 ] plus remifentanil [ 26 ] also might have myocardial protective effect. Although we did not conclude that sevoflurane had no benefit in cardiac protection compared with propofol plus remifentanil, we also could not rule out the possibility of myocardial protective effect by sevoflurane.…”
Section: Discussionmentioning
confidence: 99%